Longitudinal Study of Human Papillomavirus Persistence and Cervical Intraepithelial Neoplasia Grade 2/3: Critical Role of Duration of Infection - Rodríguez, Ana Cecilia (Oxford University Press, 2010)
BACKGROUND: The natural history of human papillomavirus (HPV) infections in older women is critical for preventive strategies, including vaccination and screening intervals, but is poorly understood. In a 7-year population-based cohort study in Guanacaste, Costa Rica, we examined whether women’s age and the duration of carcinogenic HPV infections influenced subsequent persistence of infection and risk of cervical intraepithelial neoplasia grade 2 (CIN 2) or worse disease. METHODS: At enrollment, of the 9466 participants eligible for pelvic examination, 9175 were screened for cervical neoplasia using multiple methods; those with CIN 2 or worse disease were censored and treated. Participants at low risk of CIN 2 or worse (n = 6029) were rescreened at 5–7 years (passively followed), whereas higher-risk participants (n = 2115) and subsets of low-risk women (n = 540) and initially sexually inactive women (n = 410) were rescreened annually or semiannually (actively followed) for up to 7 years. HPV testing was done using a polymerase chain reaction–based method. We determined, by four age groups (18–25, 26–33, 34–41, and ≥42 years), the proportion of prevalent infections (found at baseline) and newly detected infections (first found during follow-up) that persisted at successive 1-year time points and calculated absolute risks of CIN 2 and CIN grade 3 (CIN 3) or worse during follow-up. P values are two-sided. RESULTS: Regardless of the woman's age, newly detected infections were associated with very low absolute risks of persistence, CIN 2, or worse disease. For newly detected infections, the rate of progression to CIN 2+ (or CIN 3+), after 3 years of follow-up, was not higher for women aged 34 years and older than for younger women. Moreover, rates of newly detected infections declined sharply with age (in the actively followed group, at ages 18–25, 26–33, 34–41, and ≥42 years, rates were 35.9%, 30.6%, 18.1%, and 13.5%, respectively; P < .001). Among prevalent infections, persistent infections among older women (≥42 years) was higher than that among younger age groups or new infections at any age (P < .01 for comparison of eight groups). Most (66 of 85) CIN 2 or worse detected during follow-up was associated with prevalent infections. Only a small subset (25 of 1128) of prevalent infections persisted throughout follow-up without apparent CIN 2 or worse. CONCLUSIONS: The rate of new infections declines with age, and new infections typically do not progress to CIN 2 or worse disease in older women; thus, overall potential benefit of prophylactic vaccination or frequent HPV screening to prevent or detect new carcinogenic HPV infections at older ages is low.